Berlin - Washington, 1800 - 2000: capital cities, cultural representation, and national identities - Daum, Andreas W.; Mauch, Christof (Publications of the German Historical Institute, 2005)
Capitals in modern history: Inventing urban spaces for the nation / Andreas W. Daum -- Bundesdorf or Bundesstadt? The debates on the location of the American and German capitals / Kenneth R. Bowling and Ulrike Gerhard -- Written capitals and capital topography: Berlin and Washington in travel literature / Walter Erhart -- Prime meridians, national time, and the symbolic authority of capitals in the Nineteenth century / Martin H. Geyer -- Washington and Berlin: national capitals in a networked world / Carl Abbott -- Monumental architecture and national identity in Berlin: the case of National Socialism / Dietmar Schirmer -- Monuments of catastrophe: Holocaust architecture in Washington and Berlin / Janet Ward -- Capital gardens: the Mall and the Tiergarten / Christof Mauch -- Socialism on display: East Berlin as a capital / Brian Ladd -- Washington under Federal rule, 1871-1945 / Alan H. Lessoff -- "Everyday" protest and the culture of conflict in Berlin, 1830-1980 / Belinda Davis -- Marches on Washington and the creation of national public spaces, 1894 to the present / Lucy Barber